Effect of Socioeconomic Status and Birth Weight in Infants - Mansoor, Farah; Nikolaevna Vitkovskaya, Elizaveta; Yousif, Jehan; Effa Mujeeb, Musleh Uddin Kalar (International Journal of Innovative Research in Medical Science, 2017)
Background: Previous studies have shown that low socioeconomic status has strong influence on birth weight of newborn. Evidence has shown that as the level of socioeconomic status increases the incidence of low birth weight decreases, so socioeconomic status has direct influence on birth weight. Low birth weight (LBW) is of concern because it is associated with infant and fetal mortality. In this study we evaluated different economic, nutritional and systemic variables of the mothers which lead to low birth weight of the baby. Method: This was a descriptive cross sectional study that determined different socioeconomic factors leading to low birth weight. The study was conducted at National Institute of Child Health (NICH), Karachi. Mothers of 104 low birth weight newborns were interviewed by a self-designed questionnaire in the study. Result: Results show that 68.3% women who gave birth to LBW baby were married at the age of 18 years or below. Results also showed that 77.9% were anemic during pregnancy and 51.9% women did not increase their meals during pregnancy. Remaining 62.5% women had consanguineous marriage. Conclusion: In this study we found that young age at the time of marriage, consanguineous marriage, poor nutrition and anemia during pregnancy are greatly significant for low birth weight of baby. We strongly recommend that steps must be taken to prevent early marriages in our society, education of the mothers and provision of good prenatal and antenatal care.